2015
DOI: 10.1007/s10964-015-0325-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How Mindful Parenting May Be Linked to Mother–Adolescent Communication

Abstract: Researchers have sought to understand the processes that may promote effective parent-adolescent communication because of the strong links to adolescent adjustment. Mindfulness, a relatively new construct in Western psychology that derives from ancient Eastern traditions, has been shown to facilitate communication and to be beneficial when applied in the parenting context. In this article, we tested if and how mindful parenting was linked to routine adolescent disclosure and parental solicitation within a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 53 publications
3
56
0
5
Order By: Relevance
“…This finding suggests that biological processes may contribute to increased coping capacity and social support as habits of resilience are formed. Another study found that interventions that increased mindfulness in parenting were related to increased positive affective behavior toward children and the increased effectiveness of a parenting prevention program (Coatsworth et al, ; Lippold, Duncan, Coatsworth, Nix, & Greenberg, ). These studies suggest that attention to intrapersonal processes (e.g., processes within the parents) could contribute to relational processes and the long‐term effectiveness of parenting programs.…”
Section: The Cascading Resilience Modelmentioning
confidence: 99%
“…This finding suggests that biological processes may contribute to increased coping capacity and social support as habits of resilience are formed. Another study found that interventions that increased mindfulness in parenting were related to increased positive affective behavior toward children and the increased effectiveness of a parenting prevention program (Coatsworth et al, ; Lippold, Duncan, Coatsworth, Nix, & Greenberg, ). These studies suggest that attention to intrapersonal processes (e.g., processes within the parents) could contribute to relational processes and the long‐term effectiveness of parenting programs.…”
Section: The Cascading Resilience Modelmentioning
confidence: 99%
“…Duncan, Coatsworth, and Greenberg (2009) identifi ed fi ve key elements to mindful parenting: (1) attentive listening during parent-child exchanges; (2) being aware of, and regulating, one's own reactions; (3) attending to one's own and the child's emotions as they evolve during an exchange; (4) nonjudgmental acceptance of one's own and the child's reactions during an exchange; and (5) an overall sense of compassion and concern for oneself and the child. Such mindfulness is associated with better parent-child communication (Lippold, Duncan, Coatsworth, Nix, & Greenberg, 2015), better anger management and more positive emotion during interactions (Coatsworth, Duncan, Greenberg, & Nix, 2010), and less child noncompliance and aggression (Singh et al, 2006).…”
Section: Competent Parenting Is Mindfulmentioning
confidence: 99%
“…As a result, mindful parenting can foster more positive parent-child interactions (Coatsworth et al 2010;Dumas 2005;Duncan et al 2009a;Duncan et al 2015;Lippold et al 2015). For instance, Duncan et al (2015) found that parents with high levels of mindful parenting, compared to those with low levels, exhibited less harsh and more consistent discipline, greater warmth, more positive communication and more positive parenting behaviors in observed dyadic interactions with their children.…”
mentioning
confidence: 99%
“…Other studies have demonstrated that intervention programs aimed at promoting general mindfulness or mindful parenting can indeed increase the quality of parenting and the parent-child relationship (Bögels and Restifo 2014;Coatsworth et al 2015;Lippold et al 2015;Singh et al 2006;van der Oord et al 2012). For instance, Coatsworth et al (2010) found that mothers who participated in a mindfulness-enhanced Strengthening Families Program exhibited higher levels of mindful parenting and greater improvements in several aspects of the parent-child relationship (e.g., anger management and affective behavior towards children) when compared with mothers in a control group or who participated in the regular Strengthening Families Program (i.e., without the mindful parenting component).…”
mentioning
confidence: 99%
See 1 more Smart Citation